The Use of Board Games as Learning Media of Project Time Management - Falim, Aaron Steven; Prestiliano, Jasson (Journal of Nonformal Education, 2018)
Project time management is the ability of person to use time resources in the project to accomplish a goal efficiently. By the proper project time management, anyone can finish their jobs in the project on time. Unfortunately awareness of the importance of project time management is still lacking and not used to its full potential. Due to not using project time management properly, there are lot of delay and incomplete projects. The purpose of this research is to create a board game as media to teach peoples of the importance of project time management. This study used a mixed research approach by collecting data from the 30 college students and three companies working in game industry. Those collected datas were made into a board game named Days to Deadline that would later be used as media of instruction of project time management. By using a board game as media of time management learning, people who played the board game can learn while experiencing some fun in playing. As a result, awareness and knowledge of the importance of project time management can be perceived by the target of research. From this point, we can draw a conclusion that the board game can be used effectively to teach about the importance of good time management.